Research on folk plastic arts in interior decoration design based on big data under the environment of sustainable development - Menon, Dr.Satish (The journal of contemporary issues in business and government, 2023)
Research purpose: under the environment of modern big data technology, through the application and development of artificial intelligence, 3D modeling and other computer technologies; Bring the design field of our country from two- dimensional to three-dimensional development; By combining the traditional folk plastic arts and cultural background of our country and integrating national art into the current interior decoration design, even if the development of the design field has more innovative elements, it also provides a new channel for the inheritance and development of our folk culture and art; This paper will analyze and study the application of big data technology in indoor decoration and the integration of folk art modeling from the perspective of sustainable development, and understand the advantages of big data technology application and the impact of inheriting folk art.Through the overall effect of folk modeling art in interior decoration under sustainable development environment and ordinary environment, as well as its performance analysis and coupling under different technologies, it is statistically significant, It is obvious that the analysis and research in the environment of sustainable development is better than the previous ordinary environment. In the environment of sustainable development, interior decoration design based on big data. With the help of computer-aided integration of information technology, the combination of data and design breaks the inherent thinking mode of traditional design.Through the combination of network communication technology, As well as the virtual scene of VR technology, it can realize three-dimensional dynamic image, and can observe all corners of the space in an all-round way, so that people can have a clearer understanding of the decorative design style,computer technology, etc., and the full integration of folk plastic arts, the ideal effect of interior decoration design can be met to a great extent, making interior decoration show unique art, Help promote its development.